The Evaluation of Congenital Hypothyroidsm Screening Program in Indonesia: A Literature Review - Wahyu Setyaningsih; Ratna Dwi Wulandari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Congenital hypothyroidism is one of the main causes of mental retardation which can be prevented. Research in 2020 found that the prevalence of congenital hypothyroidism in Indonesia was 1:1167. During the previous 18 years of implementation of the Congenital Hypothyroidism Screening Program (CHSP), it was found that only 4,6% of newborns. This study aims to conduct a literature review to identify problems and obtain information on improving the implementation of congenital hypothyroidism screening programs in Indonesia. This research was carried out between November-December 2021 and consists of a review of a range of research articles and journals which have been published within the last decade. Several studies have shown that during the implementation of the CHSP, several obstacles were found which hindered the effectiveness of the program, namely the lack of training for health workers, sources of financing which have not been fully borne by the center, accuracy of collection and sample delivery, and less than optimal management function in regulating the implementation of the program thus a more in-depth evaluation needed, especially in terms of economic benefits and the level of effectiveness of the screening program. Abstrak: Hipotiroid kongenital merupakan salah satu penyebab utama keterbelakangan mental yang dapat dicegah. Penelitian pada tahun 2020 menemukan bahwa prevalensi hipotiroid kongenital di Indonesia adalah 1:1167. Selama 18 tahun terakhir pelaksanaan Congenital Hypothyroidsm Screening Program (CHSP), ditemukan hanya 4,6% bayi baru lahir. Penelitian ini bertujuan untuk melakukan studi literatur untuk mengidentifikasi masalah dan memperoleh informasi dalam meningkatkan pelaksanaan program skrining hipotiroid kongenital di Indonesia. Penelitian ini dilakukan antara November-Desember 2021 dan terdiri dari review berbagai artikel penelitian dan jurnal yang telah diterbitkan dalam dekade terakhir. Beberapa penelitian menunjukkan bahwa selama pelaksanaan CHSP ditemukan beberapa kendala yang menghambat efektifitas program, yaitu kurangnya pelatihan bagi tenaga kesehatan, sumber pembiayaan yang belum sepenuhnya ditanggung oleh pusat, ketepatan pengumpulan dan penyampaian sampel, dan kurang optimalnya fungsi manajemen dalam mengatur pelaksanaan program sehingga diperlukan evaluasi yang lebih mendalam terutama dari segi manfaat ekonomi dan tingkat efektivitas program skrining hipotiroid kongenital.